2019
DOI: 10.1108/ijqss-10-2017-0093
|View full text |Cite
|
Sign up to set email alerts
|

The effect of service recovery on customer loyalty: the role of perceived food safety

Abstract: Purpose This study aims to focus on the food industry and empirically examine the mediating role of consumers’ perceived food safety on the relationship between a company’s service recovery and customer loyalty. In addition, consumers’ demographic characteristics and their influences on the relationship between perceived food safety and customer loyalty are determined. Design/methodology/approach A survey was carried out through a structured questionnaire which was administered to the public. Using a small i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…This revealed that consumers perceived the efforts made by health authorities and market workers to improve food safety and sale conditions. Notwithstanding, these efforts must continue to improve consumer trust in street markets and similar places worldwide [ 46 , 47 , 48 ]. Consumer training in food safety must continue [ 49 , 50 ] in order to end the circular seller-consumer cycle, which provides self-feedback, and to involve everyone in food safety-related activities [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…This revealed that consumers perceived the efforts made by health authorities and market workers to improve food safety and sale conditions. Notwithstanding, these efforts must continue to improve consumer trust in street markets and similar places worldwide [ 46 , 47 , 48 ]. Consumer training in food safety must continue [ 49 , 50 ] in order to end the circular seller-consumer cycle, which provides self-feedback, and to involve everyone in food safety-related activities [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, good service recovery can help a company turn a potentially negative situation into a positive one (Gustafsson, 2009). That is, effective recovery not only can restore customer satisfaction and commitment but also can lead to loyalty (Ding and Lii, 2016;Bouranta et al, 2019;. In line with this reasoning, the following hypotheses is proposed:…”
Section: Service Recoverymentioning
confidence: 98%
“…Bougoure et al (2016) explained that if firms can handle service failures and complaints well, they can strengthen the relationship between brands and consumers because service failure and complaint management represent critical moments of truth in the relationship between brands and consumers and offer opportunities for firms to communicate with customers. This research thus suggests that effective service recovery not only corrects service failures but also enhances customers' perceptions of service quality, leads to positive word-of mouth communication, builds and maintains strong relationships and ultimately leads to customer satisfaction and loyalty (Chou, 2015;Bouranta et al, 2019). Therefore, e-commerce venders should address service failures and develop service recovery policies to resolve customers' inquiries and complaints and recover their satisfaction (Cheng et al, 2008).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 2 more Smart Citations